Attenuation Function Relationship for Far Field Earthquake Considered by Strike Slip Mechanism - Saffuan, Wan Ahmad; Azlan, Adnan; Rozaimi, Mohd Noor; Khairunisa, Muthusamy; Sk Muiz, Sk Razak; Awang, Taib; Muhd Zulham Affandi, Mohd Zahid (Trans Tech Publications, Switzerland, 2015)
An attenuation relationship for far field earthquakes considered by strike slip has been developed. The attenuation relationship function was develop using regression analysis. The database consisting of more than 130 peak ground accelerations from seven earthquake sources recorded by Seismology Station in Malaysia have been used to develop the relationship. This study aims to investigate the new relationship attenuation to gain exact peak ground acceleration at the location on site. Based on this study, the location is a structure located at Terengganu seaside.